Phaseolus germplasm exploration - Debouck, Daniel G. (Springer, 1988)
The following aspects to be considered in germplasm collection are analyzed: definition of the genus being looked for, centers of diversity, strategy, contacts, equipment, itinerary, sampling methods of cultivated and wild materials, collector's name and no., place of collection (name, lat., longitude, alt., country, state or province, district or county), date of collection, and common or vernacular name. Germplasm explorations should be carried out to collect the broadest possible range of genetic variability rather than variability pertaining to current breeding objectives. (CIAT)